Empowerment as a Pivotal Deterrent to Employee Silence: Evidence from the UAE Hotel Sector. Issue 2 (15th March 2021) - Bani-Melhem, Shaker; Zeffane, Rachid; Abukhait, Rawan; Shamsudin, Faridahwati Mohd.
ABSTRACT: Based on time-lagged data focusing on frontline employees (N=285) operating in five-star hotels in the United Arab Emirates (UAE), we examined the individual and combined effects of empowerment, job satisfaction, and perceived organizational support on employee silence. Using structural equation modeling for data analysis, we explored a hypothetical model. The results indicated that empowerment had a significant negative impact on employee silence while job satisfaction and perceived organizational support had no significant direct impact. However, these latter two variables had an impact when feelings of empowerment were also present. The result suggests indicates that empowerment plays a central (pivotal) role in silence behavior. The implications of these findings for both management practice and future research are discussed.